PERAN TABUNGAN DALAM MENGHIMPUN DANA PIHAK KETIGA MASA PANDEMI COVID-19 PADA BANK SUMUT KCP SYARIAH SIMPANG KAYU BESAR - Yusuf Yusuf; Nurul Jannah; Hamdani Achmad (Nurul Jadid University, 2022)
The development of banking in Indonesia is currently relatively stable and continues to grow; this study aims to determine the role of savings in raising third-party funds at Bank Sumut Syariah KCP Simpang Kayu Besar. The research method used in this research is qualitative research with descriptive analysis technique. The source of the data in this research is the primary data is interviewed by the bank, and the secondary data in this study is a literature study. The bank usually collects third-party funds from the public by using the bank's products consisting of demand deposits, savings and time deposits. At PT. Bank Sumut Syariah KCP Simpang Kayu Besar DPK was very high on deposit products in 2019; during the Covid-19 pandemic, stakes could have been more helpful in increasing the bank's DPK. Savings are essential in growing third-party funds at Bank Sumut Syariah KCP Simpang Kayu Besar.